Mediating impact of fan-page engagement on social media connectedness and followers purchase intention - Rahman, Zoha; Moghavvemmi, Sedigheh; Suberamanian, Kumaran; Zanuddin, Hasmah; Md Nasir, Mohd Hairul Nizam (Emerald, 2018)
Purpose: The purpose of this paper is to identify the mediating effect of fan-page followers’ engagement activities and moderating role of followers’ demographic profile and trust level on their purchase intention. Design/methodology/approach: This study utilised the customer engagement behaviour and consumer involvement theory as a foundation to explore the impact of variables. Structural equation modelling was utilised to test the model with the data collected from 307 Facebook fan pages’ followers of five Malaysian companies. Findings: It was shown that following fan pages will influence fan page engagement, which in turn affects purchase intention and social media connectedness. Further analysis indicated that the impact of “follow” and “engagement” on purchase intention differs between genders, ages, level of trust and income. Research limitations/implications: The study serves as a basic fundamental guideline for academics and researchers to interpret the concept of following fan pages and engagement actions and its effects on purchase intention and social media connectivity, as well as opening a vast area of unexplored researches on the subject of social media. Practical implications: The research provides information for business-to-consumer companies in utilising fan page based on user categories. Originality/value: This study proposes the application of an empirically tested framework to the fan-page follow actions. The authors argue that this framework can provide a useful foundation for future social commerce research. The results would help academics be aware of fan page and its user’s engagement actions, which will provide a new avenue of research.